Bacterial contamination of cotton as an indicator of respiratory effects among card room workers. Issue 4 (November 1979) - Rylander, R; Imbus, H R; Suh, M W
Abstract : The influence of the bacterial contamination of cotton dust on the development of pulmonary symptoms has been investigated. The pulmonary function of card room workers in 23 US cotton mills was tested before and after the Monday working shift. A significant relation was found between the delta FEV1.0 decrement and the vertical elutriator dust level in the different mills. An improved correlation was obtained when the number of Gram-negative bacteria cultured from the bale cotton used in the different mills was employed in the exposure description. The results support earlier epidemiological and experimental studies, which demonstrate the importance of the Gram-negative bacteria in the development of pulmonary symptoms among workers in cotton mills.